To evaluate the role of interleukin-6 in alopecia areata - Wali Muhammad, Sobia; Pirzado, Muhammad Suleman (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the level of interleukin-6 in alopecia areata patients. Method: The exploratory study was conducted from September to December 2021 at the Sindh Institute of Skin Disease, Karachi, and comprised alopecia areata patients regardless of age and gender in group A, while healthy controls matched for age and gender formed group B. Alopecia areata classification and severity were done using the Severity of Alopecia Tool. Serum interleukin-6 was measured using enzyme-linked immune sorbent assay. Data was analysed using R statistical software v4.2.1. Results: Of the 100 subjects, 50(50%) with mean age 15.52+/-10.14 years were cases in group A; 26(52%) females with mean age 16.78±10.77 years, and 24(48%) males with mean age 16.44±10.3 years. The remaining 50(50%) were controls in group B. Interleukin-6 concentration was significantly higher in group A (p<0.05). The concentration was not significantly different between the genders (p>0.05). The concentration was the highest in patients aged 11-20 years, followed by 21-30 years, 31-40 years and 1-10 years. Conclusion: The concentration of circulatory pro-inflammatory interleukin-6 was significantly higher in alopecia areata patients than in the healthy controls. Key Words: Alopecia areata, Autoimmune, Cytokines, Interleukin-6, Skin disease.